Competitive Strategies of Maktour in Digital Competition and Strengthening the Ummah Economy - Khoiruddin Ali Rahman; Muhamad Zen; Fatmawati (Universitas Muhammadiyah Ponorogo, 2026)
Introduction/Main Objectives: The rapid development of digital platforms has transformed competition in the Hajj and Umrah travel industry by reshaping consumer behavior, marketing practices, and service delivery systemsThis study aims to analyze the competitive strategies implemented by Maktour in responding to digital platform competition and to examine its contribution to strengthening the ummah economy. Background Problems: This topic is important because increasing digitalization has intensified competition among travel agencies, while studies integrating competitive strategy, digital competition, and the ummah economy remain limited. Novelty: The novelty of this research lies in the integration of strategic management and Islamic economics perspectives to explain how competitive advantage can support both business sustainability and socio-economic development. Research Methods: This study employs a qualitative descriptive-analytical approach using a literature review method. Data were collected from academic journals, company documents, official reports, and credible digital sources related to competitive advantage, digital transformation, and Islamic economics. Findings/Results: The findings reveal that Maktour adopts a multidimensional competitive strategy through service differentiation, digital marketing optimization, trust-based customer relationship development, and the integration of Islamic values into business practices. These strategies strengthen the company’s competitive position by emphasizing premium services, spiritual guidance, and customer trust while adapting to technological changes. Furthermore, Maktour contributes to strengthening the ummah economy through employment generation, support for sharia-based business ecosystems, and multiplier effects in related sectors. Conclusion: The study concludes that sustainable competitive advantage in the Hajj and Umrah industry depends not only on technological adaptation and operational efficiency but also on spiritual values, service quality, and long-term customer trust.